Lactic Acid Transport Mediated by Aquaporin-9: Implications on the Pathophysiology of Preeclampsia - Medina, Yollyseth; Acosta, Lucas; Reppetti, Julieta; Corominas, Ana; Bustamante, Juanita; Szpilbarg, Natalia; Damiano, Alicia E. (Frontiers in Physiology, 2021)
AQP9 expression is significantly increased in preeclamptic placentas, but it is not functional. Since feto-maternal Aquaporin-9 (AQP9) expression is significantly increased in preeclamptic placentas. Since feto-maternal water transfer is not altered in preeclampsia, the main role of AQP9 in human placenta is unclear. Given that AQP9 is also a metabolite channel, we aimed to evaluate the participation of AQP9 in lactate transfer across the human placenta. Explants from normal term placentas were cultured in low glucose medium with or without L-lactic acid and in the presence and absence of AQP9 blockers (0.3mM HgCl2 or 0.5mM Phloretin). Cell viability was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay and lactate dehydrogenase (LDH) release. Apoptotic indexes were analyzed by Bax/Bcl-2 ratio and TUNEL assay. Heavy/large and light/small mitochondrial subpopulations were obtained by differential centrifugation, and AQP9 expression was detected by Western blot. We found that apoptosis was induced when placental explants were cultured in low glucose medium while the addition of L-lactic acid prevented cell death. In this condition, AQP9 blocking increased the apoptotic indexes. We also confirmed the presence of two mitochondrial subpopulations which exhibit different morphologic and metabolic states. Western blot revealed AQP9 expression only in the heavy/large mitochondrial subpopulation. This is the first report that shows that AQP9 is expressed in the heavy/large mitochondrial subpopulation of trophoblasts. Thus, AQP9 may meditate not only the lactic acid entrance into the cytosol but also into the mitochondria. Consequently, its lack of functionality in preeclamptic placentas may impair lactic acid utilization by the placenta, adversely affecting the survival of the trophoblast cells and enhancing the systemic endothelial dysfunction.